STUDI KASUS TEKNIK RADIOGRAFI COLON IN LOOP PEDIATRIK DENGAN KLINIS INVAGINASI DI INSTALASI RADIOLOGI RSUD MUNTILAN - Wardah Fauziyah,; Ari Anggraeni,; Widya Mufida, (Journal of Innovation Research and Knowledge, 2025)
Background: A pediatric colonoscopy for clinical intussusception was conducted at the Radiology Department of RSUD (Regional General Hospital) Muntilan without preoperative preparation, utilizing plain anteroposterior, lateral, and AP single-contrast projections with a total volume of approximately 1200 ml of BaSO₄. Differences were observed in the examination procedure and contrast volume compared to Mahardika's study conducted at the Dr. Moewardi Regional Hospital Radiology Department in Surakarta. This study aims to determine the best technique for conducting a pediatric colonoscopy in cases of clinical intussusception, the justification for employing BaSO₄, and the appropriate volume of contrast media used. Method: This study employed a qualitative methodology utilizing a case study approach. The research was carried out at the Radiology Department of Muntilan Regional Hospital between May and June 2025. The participants included three radiographers and one radiologist. The research was carried out in the colonoscopy department. Data were collected through interviews and documentation. Data were subsequently analyzed using data reduction, data presentation, and conclusion drawing methods. Result: The pediatric colonoscopy procedure for clinical intussusception at the Muntilan Regional Hospital Radiology Department is conducted without patient preparation. Barium sulfate (BaSO₄) is utilized as the contrast medium to generate hydrostatic pressure on the intussusception, anticipated to facilitate its release. The total volume of contrast medium is approximately 1200 ml, requiring reinsertion to adequately fill the entire colon and cecum due to contrast reflux. The anteroposterior projection facilitates visualization of the entire colon, while the lateral projection is employed to examine the sigmoid colon and rectum. Both anteroposterior and lateral projections are adequate for anatomical presentation and diagnosis. Conclusion: The pediatric colonoscopy procedure for clinical intussusception at the Muntilan Regional Hospital Radiology Department is conducted without patient preparation. Approximately 1200 ml of barium sulfate (BaSO₄) contrast medium is administered due to contrast reflux. The anteroposterior and lateral projections are adequate for diagnostic purposes